Ultracold neutron storage in a bottle coated with the fluoropolymer CYTOP - Neulinger, Thomas; Beck, Douglas; Connolly, Euan; Degenkolb, Skyler; Fierlinger, Peter; Filter, Hanno; Hingerl, Jürgen; Nordin, Pontus; Saerbeck, Thomas; Zimmer, Oliver (The European physical journal. A, Hadrons and nuclei, 2022)
The fluoropolymer CYTOP was investigated in order to evaluate its suitability as a coating material for ultracold neutron (UCN) storage vessels. Using neutron reflectometry on CYTOP-coated silicon wafers, its neutron optical potential was measured to be 115.2(2) neV. UCN storage measurements were carried out in a 3.8 l CYTOP-coated aluminum bottle, in which the storage time constant was found to increase from 311(9) s at room temperature to 564(7) s slightly above 10 K. By combining experimental storage data with simulations of the UCN source, the neutron loss factor of CYTOP is estimated to decrease from 1.1(1)$$× 10^{-4}$$to 2.7(2)$$× 10^{-5}$$at these temperatures, respectively. These results are of particular importance to the next-generation superthermal UCN source SuperSUN, currently under construction at the Institut Laue-Langevin, for which CYTOP is a possible top-surface coating in the UCN production volume.
Gesehen am 05.09.2022